Acid-base and Electrolyte Disturbances in Children Presenting with Acute Watery Diarrhoea in Emergency Observation and Referral Unit of Dhaka Shishu (Children) Hospital - Tayab, Md Abu; Hoq, Md Ariful (Dhaka Shishu (Children) Hospital Journal, 2021)
Background: Acute watery diarrhoea (AWD) is a leading cause of illness and death amongst children in developing countries. Electrolyte and acid-base disturbances play an important role in the associated morbidity and mortality. Objectives: To observe the acid-base and electrolyte changes in moderate and severe dehydration in AWD in children. Methods: This cross sectional study was carried out in the Observation and Referral Unit of Dhaka Shishu (Children) Hospital from July 2018 to December 2018. Children below five years of age who came with acute diarrhoea with moderate to severe dehydration were included in the study. After admission 2ml of whole blood was collected with all aseptic measures at the time of insertion of intravenous cannula before giving intravenous fluids to measure serum levels of Na and K while arterial blood was also taken for analysis. The data was analyzed by using SPSS version 20. Results: Total 125 AWD cases were admitted among them 98(78.4%) had moderate dehydration whereas 27(21.6%) had severe dehydration. Hyponatremic dehydration was present in 41(32.8%) cases. Among them 30(30.6%) had moderate dedydration and 11(40.4%) had severe dehydration, hypernatremic dehydration was present in 11.11% cases, hypokalemia was present in 54(43.2%) cases. Among them 42(42.86%) had moderate dedydration and 12(44.44%) had severe dehydration. Metabolic acidosis was present in 38(30.4%) cases [28(28.57%) in moderate dedydration and 10(37.04%) in severe dehydration]. The comparison of mean serum sodium and potassium value of the children with moderate and severe degrees of dehydration did not attain statistical significance, but there was a significant difference in bicarbonate concentration among moderate and severe dehydration cases (p=0.02). Conclusion: Hyponatremia and hypokalamia was the commonest electrolyte abnormality among moderate to severe dehydration with AWD. Mean serum sodium and potassium of the children with moderate and severe degrees of dehydration did not attain statistical significance, but bicarbonate concentration was significantly low among severe dehydration cases. DS (Child) H J 2020; 36(2): 120-124